Analysis of Parity and Socio-Cultural Factors Influencing Nutritional Status of Pregnant Women in the Working Area of Itlay Hisage Community Health Center, Jayawijaya Regency - Riza Faulina; Arianti Hernida; Dina Paliling; Erlina Hasiholan S; Meisa Andriani; Merlin Arisla Malapu; Millya Kristi Sahentumbage (Jurnal Penelitian Pendidikan IPA, 2025)
Analysis of Parity and Socio-Cultural Factors Influencing Nutritional Status of Pregnant Women in the Working Area of Itlay Hisage Community Health Center, Jayawijaya Regency